Analysis and Evaluation of the Progressive Collapse of Cable Dome Structures Induced by Joint Damage - Lian-Meng Chen; Kai-Yu Huang; Yi-Jie Liu; Ze-Bin Li; Yi-Hong Zeng; Wei Li; Yi-Yi Zhou; Shi-Lin Dong (Buildings, 2023)
The current literature lacks an effective progressive collapse analysis of a cable dome structure induced by joint damage. In this study, a dynamic analysis was performed using actual construction cases, an ANSYS LS-DYNA analysis platform, and a fully dynamic equivalent load instantaneous removal method. First, the structure’s dynamic responses and collapse modes induced by different joints with different types of damage were explored. Subsequently, joint importance coefficients were proposed depending on the structure’s displacement before and after joint removal, and the relationships between the joint importance coefficients and the joint properties and collapse modes, respectively, were then identified. Finally, the relationship between the joint damage and the connected component damage was explored. The results revealed that different joints and identical joints with different types induced a variety of dynamic responses. However, the dynamic response induced by the discontinuous joint damage was more apparent than that induced by the continuous joint damage. When a continuous joint model was used, the damage on all joints did not result in the progressive or local progressive collapse of the structure. Thus, all these joints were considered as common joints. However, when a discontinuous joint model was used, the failure of the joints resulted in three distinct collapse modes, namely a progressive collapse, a local progressive collapse, and a nonprogressive collapse, corresponding to the key joints, the important joints, and the common joints, respectively. These three types of joints corresponded to different importance coefficients. When damage occurred in the discontinuous joints separately linked to the key components, the important components, and the common components, the joints resulted in the progressive collapse, local progressive collapse, and nonprogressive collapse, respectively, of the structure.